Are omega-3 fatty acids safe and effective in acute pancreatitis or sepsis? A systematic review and meta-analysis. Issue 9 (September 2020) - Wolbrink, Daniel R.J.; Grundsell, Jessica R.; Witteman, Ben; Poll, Marcel van de; Santvoort, Hjalmar C.van; Issa, Eyad; Dennison, Ashley; Goor, Harry van; Besselink, Marc G.; Bouwense, Stefan A.W.
Summary: Background: Acute pancreatitis (AP) is marked by a strong pro-inflammatory response, which may cause a systemic inflammatory response syndrome (SIRS), organ failure, and death. Early administration of omega-3 fatty acids (FA) may reduce the pro-inflammatory response and improve outcome in AP. A systematic review focusing on the safety and efficacy of omega-3 FA in AP is lacking. Aim: Evaluate the safety and efficacy of an intervention with omega-3 FA in acute pancreatitis and additionally in sepsis. Methods: A systematic review and meta-analysis was performed using the PubMed, Embase, and Cochrane databases including only randomized controlled trials in AP and, for safety endpoints, in sepsis investigating intervention including omega-3 FA without other active components (e.g. addition of glutamine to the intervention). The primary outcome was mortality. Results: After screening 1186 studies, five randomized trials (n = 229) with omega-3 FA in AP were included. In AP patients treated with omega-3 FA within 48 h after hospitalization, a non-significant reduction of mortality was seen (OR 0∙50, 95%CI 0∙13–1∙99, p = 0∙33), compared to controls. In two studies (n = 85), omega-3 FA reduced the risk of new onset of organ failure (OR 0∙33, 95%CI 0∙12–0∙93, p = 0∙04). Nine randomized trials with 312 patients suffering from sepsis (not pancreatitis related) demonstrated a reduced mortality (OR 0∙52, 95%CI 0∙28–0∙97, p = 0·04). None of these 14 randomized trials reported safety concerns. Conclusions: Administration of omega-3 FA could reduce the risk of new-organ failure in patients with AP. There were no safety issues reported of the early administration of omega-3 FA in any of the included studies. To show the real clinical benefit of omega-3 FA in AP, a large and pragmatic randomized controlled trial is needed.